A FAMÍLIA COMO CENÁRIO DE CUIDADO FORMAL: como os enfermeiros percebem o seu cuidado à família na Estratégia Saúde da Família? - Aragão, Mónica Andréa Miranda (2014)
The nurses of the Family Health Strategy should build with families in a cooperative relationship - professional / family, based on a theoretical grounding, allied the technological and scientific knowledge with observation skills, communication and intuition. Aimed to with this work understanding the practice of nurses of the Family Health Strategy in family care. This is a descriptive study with a qualitative approach, done in eight basic health units, with nurses of the Family Health Strategy. The semi-structured interview was used. The data collection survey was conducted in the period February to May 2014, with analysis of data from the thematic analysis. After analytical-reflective process of interviews, emerged 640 (six hundred and forty) nucleus of meaning, which have been grouped into seventeen (17) provisional themes and 03 (three) final themes: knowing the families served; featuring your work process in the family health strategy; and taking care of the family on the family health strategy. These themes reflect that nurses know the characteristics of families served, a fact that helps the family in the care process. Featuring the work process in the strategy as a reflection of the guidelines recommended by the Ministry of Health, but with little effectiveness in caring for families served. Conceptualize the family as a group of people united by kinship or not, who perceive themselves as a family, that have common objectives and mutually care if. The family care despite believing that exceeded the model and focusing on individuals who can take care of the family as the context of health and disease, do not have the methodologies for assessment and intervention of families do not know and do not use this for care tools, focus is the individual in the family; reported that family care is not put into practice due to structural problems, such as lack of car for home visits, view this as a major tool for approaching families. Show that they feel frustrated and distressed for not realizing their professional value and recognition of their work on strategy. It is concluded that formal care practiced by nurses to families, requires a reflection on what is actually working toward families, adopting methodological strategies for the effective planning of actions directed to the care of families.